2006
DOI: 10.1016/j.jtbi.2005.06.027
|View full text |Cite
|
Sign up to set email alerts
|

An analytical estimation of the energy cost for legged locomotion

Abstract: Legged locomotion requires the determination of a number of parameters such as stride period, stride length, order of leg movements, leg trajectory, etc. How are these parameters determined? It has been reported that the locomotor patterns of many legged animals exhibit common characteristics, which suggests that there exists a basic strategy for legged locomotion. In this study we derive an equation to estimate the cost of transport for legged locomotion and examine a criterion of the minimization of the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 42 publications
3
30
0
Order By: Relevance
“…However, given the exceptional skeletal evidence for a heterogeneously partitioned pulmonary apparatus in saurischian dinosaurs and pterosaurs, it is important to note that such pulmonary systems in extant sauropsids also occupy a significant volume of the body cavity (see Duncker,'79;Perry,'83;Duncker and Güntert,'85). Thus, whole body mass estimates in fossil archosaurs (e.g., Wedel, 2005Wedel, , 2007Schwarz and Fritchs, 2006) and any associated energetic considerations for whole body mechanics (e.g., turning inertia [Carrier et al, 2001], cost of transport [Nishii, 2006]) or thermoregulation (Perry et al, this volume) must account for those portions of the anatomy (e.g., intrathoracic and intraabdominal air sacs) not predicted to directly impact skeletal morphology in preserved fossils of these taxa. For example, recent modeling efforts (Hutchinson et al, 2007) have explicitly attempted to model locomotor biology in extinct archosaurs using a range of estimates for whole trunk density based on different models of pulmonary structure.…”
Section: Controls On Skeletal Pneumatization: Systemic Local or Both?mentioning
confidence: 99%
“…However, given the exceptional skeletal evidence for a heterogeneously partitioned pulmonary apparatus in saurischian dinosaurs and pterosaurs, it is important to note that such pulmonary systems in extant sauropsids also occupy a significant volume of the body cavity (see Duncker,'79;Perry,'83;Duncker and Güntert,'85). Thus, whole body mass estimates in fossil archosaurs (e.g., Wedel, 2005Wedel, , 2007Schwarz and Fritchs, 2006) and any associated energetic considerations for whole body mechanics (e.g., turning inertia [Carrier et al, 2001], cost of transport [Nishii, 2006]) or thermoregulation (Perry et al, this volume) must account for those portions of the anatomy (e.g., intrathoracic and intraabdominal air sacs) not predicted to directly impact skeletal morphology in preserved fossils of these taxa. For example, recent modeling efforts (Hutchinson et al, 2007) have explicitly attempted to model locomotor biology in extinct archosaurs using a range of estimates for whole trunk density based on different models of pulmonary structure.…”
Section: Controls On Skeletal Pneumatization: Systemic Local or Both?mentioning
confidence: 99%
“…Many experimental and theoretical studies have reported that locomotor parameters, such as stride length and frequency, are optimized based on energy cost [2,3,4,5,6,7]. However, the choice of leg swing trajectory during walking is still under debate.…”
Section: Constraint On Redundant Degrees Of Freedommentioning
confidence: 99%
“…The first term represents mechanical energy and the second term is related to energy loss by heat emissions. Although a negative value for the first term, i.e., mechanical energy indicates a gain in energy supplied by external forces, DC motor cannot store this energy [20,21]. Therefore, the energy consumed by the DC motor during time T is given by…”
Section: Energy Consumption Of a Six-legged Robotmentioning
confidence: 99%